Back Cover: Recyclable Bifunctional Polystyrene and Silica Gel‐Supported Organocatalyst for the Coupling of CO2 with Epoxides (ChemSusChem 12/2015). Issue 12 (22nd June 2015) - Kohrt, Christina; Werner, Thomas
<x xml:space="preserve">Abstract</x> The Back Cover picture shows a bifunctional ammonium salt covalently bound to a silica support catalyzing the addition of carbon dioxide to epoxides under solvent‐free conditions. The catalysts can be easily recovered by simple filtration after the reaction and reused in up to 13 consecutive runs with retention of high activity and selectivity even at 90 °C. The scope and limitations of the reaction have been evaluated in terms of reaction conditions and substrate scope. More details can be found in the Communication by Kohrt and Werner (DOI: 10.1002/cssc.201500128).